AB0270 Treatment response to rituximab in combination with leflunomide is influenced by anticcp status in active rheumatoid arthritis: results from a multicenter randomised placebo-controlled investigator initiated clinical trial in active rheumatoid arthritis (AMARA-STUDY). (12th June 2018) - Köhm, M.; Rossmanith, T.; Alten, R.; Aringer, M.; Backhaus, M.; Burmester, G.; Feist, E.; Herrmann, E.; Kellner, H.; Lehn, A.; Müller-Ladner, U.; Rubbert-Roth, A.; et al.
Abstract : Background: Use of biologicals such as Rituximab (RTX) in Rheumatoid Arthritis (RA) is effective and often only licensed in combination with Methotrexate (MTX). In cases of contraindications to or intolerances, other cDMARDs are frequently used in routine care without data from RCTs. Patients with positive antiCCP-status were identified in previous studies to better respond to RTX in combination with MTX. Objectives: Here we present for the first-time data of the impact of antiCCP status on ACR response in the combinational therapy of RTX and Leflunomide (LEF). Methods: A total of 189 patients with active RA (DAS28 >3.2 and at least 3 SJC and 3 TJC) despite stable LEF treatment were screened for a 52 weeks double-blind placebo controlled multicenter RCT. Patients were randomised to receive either two times 1000 mg RTX i.v. or PLA, followed by a second course of RTX of either two times 500 or 1000 mg at week 24. The primary endpoint of the study was superiority of RTX in ACR20 and 50 responses during 24 weeks treatment period. Adult patients who had inadequate response to more than one antiTNF or failed more than three cDMARDs were excluded. Disease activity was measured at each visit and compared according to antiCCP status. For safety evaluation, frequency and severity of adverse events were documented. Results: Of 189 screened patients 148 were randomised. The mean age was 56 years; the mean body weight 76 kg and 74% were female. The disease activity (DAS28) at baseline was 5.57 for RTX and 5.54 for PLA. 57.1% of the patients were antiCCP-positive for RTX compared to 59.6% for PLA. In the RTX group, antiCCP-positive patients' disease duration was 8.8 years compared to 5.6 years in the antiCCP-negative group), DAS28 was 5.73 vs. 5.32 and CRP levels were 11.1 mg/L vs. 5.3 mg/L. RTX demonstrated significant superiority compared to PLA at week 16 in both, ACR 20 and ACR 50 response. AntiCCP-positive patients showed a higher probability to respond to the RTX/LEF treatment than antiCCP-negative patients (figure 1). 43 serious adverse events were reported, 27 of them in the RTX treatment group during the placebo-controlled period. Conclusions: Here we report data of the first RCT investigating the combination of RTX with LEF in RA. The treatment with RTX in combination with LEF demonstrated significant efficacy compared to PLA for ACR20 and 50 responses with highest response level at week 16. AntiCCP-positive patients showed a higher probability for treatment response compared to antiCCP-negative ones. The combination of RTX and LEF demonstrated a reasonable safety profile. Disclosure of Interest: M. Köhm Grant/research support from: Janssen, Roche, Pfizer, Speakers bureau: Novartis, Janssen, Celgene, Pfizer, T. Rossmanith: None declared, R. Alten: None declared, M. Aringer: None declared, M. Backhaus: None declared, G. Burmester: None declared, E. Feist: None declared, E. Herrmann: None declared, H. Kellner: None declared, A. Lehn: None declared, U. Müller-Ladner: None declared, A. Rubbert-Roth: None declared, H.-P. Tony: None declared, S. Wassenberg: None declared, H. Burkhardt: None declared, F. Behrens: None declared